2000
DOI: 10.1385/bter:77:1:25
|View full text |Cite
|
Sign up to set email alerts
|

Indication of Silicon Essentiality in Humans : Serum Concentrations in Belgian Children and Adults, Including Pregnant Women

Abstract: Serum silicon concentrations were determined in Belgian healthy children and adults, including pregnant women, by electrothermal atomic absorption spectrometry. Serum levels appeared to be significantly higher in healthy children (1-18 yr) than in healthy adults (19-60 yr). Especially, levels in infants (< 1 yr) were higher than in any other group. Compared to age-matched nonpregnants, the serum silicon content was very low in pregnant women. In addition to the fact that this study for the first time provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 13 publications
8
56
6
Order By: Relevance
“…[32] It is an essential nutrient for the natural ecosystem in general, [33] and for humans and other vertebrates in particular, [32,34] where silicon deprivation results in severe skeletal malformations. [35] The highest silicon concentrations were determined in avian connective tissue, compared to heart or muscle tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[32] It is an essential nutrient for the natural ecosystem in general, [33] and for humans and other vertebrates in particular, [32,34] where silicon deprivation results in severe skeletal malformations. [35] The highest silicon concentrations were determined in avian connective tissue, compared to heart or muscle tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a burst of silicon accumulation was seen around the osteoid and osteoid-bone interfaces, suggesting that this inorganic component is essential for bone formation. [32][33][34][35] Previous studies demonstrate that bio-silica combines two highly valued properties: it is osteoinductive [24,25] and it operates as a biologized, solid matrix for cells that control hydroxyapatite formation. [25] The present study aims to explore these properties in the context of a novel bonesubstitution material.…”
Section: Introductionmentioning
confidence: 99%
“…Biosilica is an essential nutrient for the natural ecosystem in general, [75] and for humans and other vertebrates in particular, [76,77] where silicon deprivation results in severe skeletal malformations. [78] Thus, in avian connective tissue the highest silicon concentrations have been determined as compared to heart or muscle tissue.…”
Section: Biomedical Approachmentioning
confidence: 99%
“…Silicon concentration in blood remains relatively constant, implying rapid distribution to tissues or excretion into the urine. While early analyses showed that serum contains 50-60 µg silicon/dL (Dobbie and Smith, 1982;Carlisle, 1984), more recent analyses indicate that human serum contains 11-25 µg silicon/dL (Van Dyck et al, 2000;Calomme et al, 1998). Exceptions included pregnant women who had very low serum silicon concentrations (3.3-4.3 µg/dL) and infants who had higher concentrations (34-69 µg/dL).…”
Section: General Information On the Metabolic Fate Of Siliconmentioning
confidence: 99%